Influence Understanding Taxation and Awareness Must Tax to Compliance MSME Tax - Mega Mustika Sari (Sekolah Tinggi Agama Islam Kuningan, 2025)
Taxes are the primary source of funding for development in Indonesia, with Micro, Small, and Medium Enterprises (MSMEs) contributing significantly to GDP. However, MSMEs' tax compliance remains low, primarily due to limited tax understanding and taxpayer awareness. This study aims to address this issue by analyzing the influence of these two factors on tax compliance. This study aims to analyze the influence of tax understanding and taxpayer awareness on MSME tax compliance in Indonesia and to provide recommendations for improving compliance through education and outreach. This study used a quantitative approach with a causal survey design among 400 MSMEs in Central Java and Yogyakarta. Data were collected through questionnaires and analyzed using Structural Equation Modeling (SEM) was used to test the hypothesis. The results showed that tax understanding (coefficient 0.45) and taxpayer awareness (coefficient 0.38) significantly influenced tax compliance, although the compliance rate only reached 45%. Understanding had a greater influence than awareness, indicating the need for educational interventions to improve MSME compliance.